EFEKTIVITAS PEMBELAJARAN FISIKA BERBASIS MULTIREPRESENTASI UNTUK MELATIH KEMAMPUAN REPRESENTASI SISWA - Tresni Widyawati Widyawati; Yennita '; Hendar Sudrajad Sudrajad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The aim of this research is to determine the effectiveness of learning physics-based multiple-representations to train students representation capability in the Newton's Law Subject. The expected benefits of this research is as a basis for further examine the success rate of students by using a lot of other learning approaches. This research was conducted at MAN 1 Pekanbaru precisely in October 2014 to January2015 in class X Science totaling 29 students. The design of the research is Pre-experimental design form one group pretest-posttest. From the research, based on indicators of Representation ability; formulate information from a representation, the consistency of representation and solve problems using the representation obtained gain with high category that was declared that learning effectiveness is effective. As for the aspect of forming a new representation obtained gain in the category medium so that the effectiveness is effective enough. Furthermore, the ability of t students to present the representation seen in various forms of representation;, verbal representation, mathematical representation, and graphs representation obtained gain with high category and for the pictorial representation obtained gain in medium category. Average score of all indicators on the pretest and posttestobtained gain with high category. So it can be concluded that learning physics with multiple representations effective to train student representation ability in MAN 1 Pekanbaru class X in Newton’s Law Subject. Key Words : learning effectiveness,multiple-representations, representation ability, Netwton’s law